Ill-health and labour market outcomes in Uganda - Matovu, Fred; Birungi, Patrick; Sebaggala, Richard (The African Economic Research Consortium, 2009)
The role health plays in reducing poverty and economic development particularly in developing countries is undisputable in the economic literature (Audibert, 2009) Health of the population is a key factor for labor productivity, poverty reduction and overall economic development. Healthier workers are physically and mentally more energetic and robust; productive and tend to earn higher wages; and they are also less likely to be absent from work because of illness (or illness in their family) (Bloom et al, 2004). Most recently, the links between population health and economic productivity have become a significant policy concern (Tompa, 2002). In Uganda, although the national health indicators look good, ill health is a growing problem in both rural and urban areas, particularly among the poor. The improvement health indicators have been largely brought about by efficiency gains rather than big increases in overall health sector resource envelope. Therefore, there is feeling among policy makers and researchers that if spending in the health sector is increased, the 75% preventable disease burden can be reduced enormously.